Temperature-induced modulation of stress-tolerant PGP genes bioprospected from Bacillus sp. IHBT-705 associated with saffron (Crocus sativus) rhizosphere: A natural -treasure trove of microbial biostimulants - Ali, Nilofer; Swarnkar, Mohit Kumar; Veer, Raj; Kaushal, Priya; Pati, Aparna Maitra (Frontiers in Plant Science, 2023)
There is a renewed interest in sustainable agriculture wherein novel plant growth-promoting rhizobacteria (PGPR) are being explored for developing efficient biostimulants. The key requirement of a microbe to qualify as a good candidate for developing a biostimulant is its intrinsic plant growth-promoting (PGP) characteristics. Though numerous studies have been conducted to assess the beneficial effects of PGPRs on plant growth under normal and stressed conditions but not much information is available on the characterization of intrinsic traits of PGPR under stress. Here, we focused on understanding how temperature stress impacts the functionality of key stress tolerant and PGP genes of Bacillus sp. IHBT-705 isolated from the rhizosphere of saffron (Crocus sativus). To undertake the study, Bacillus sp. IHBT-705 was grown under varied temperature regimes, their PGP traits were assessed from very low to very high-temperature range and the expression trend of targeted stress tolerant and PGP genes were analyzed. The results illustrated that Bacillus sp. IHBT-705 is a stress-tolerant PGPR as it survived and multiplied in temperatures ranging from 4°C-50°C, tolerated a wide pH range (5-11), withstood high salinity (8%) and osmolarity (10% PEG). The PGP traits varied under different temperature regimes indicating that temperature influences the functionality of PGP genes. This was further ascertained through whole genome sequencing followed by gene expression analyses wherein certain genes like cspB, cspD, hslO, grpE, rimM, trpA, trpC, trpE, fhuC, fhuD, acrB5 were found to be temperature sensitive while, cold tolerant (nhaX and cspC), heat tolerant (htpX) phosphate solubilization (pstB1), siderophore production (fhuB and fhuG), and root colonization (xerC1 and xerC2) were found to be highly versatile as they could express well both under low and high temperatures. Further, the biostimulant potential was checked through a pot study on rice (Oryza sativa), wherein the application of Bacillus sp. IHBT-705 improved the length of shoots, roots, and number of roots over control. Based on the genetic makeup, stress tolerance potential, retention of PGP traits under stress, and growth-promoting potential, Bacillus sp. IHBT-705 could be considered a good candidate for developing biostimulants.